Frequency of ABO and Rh blood groups in Healthy Donors - Muhammad Iqbal , Alauddin Niazi , Mohammad Tahir (Journal of Rawalpindi Medical College, 2009)
Background: To document the frequency of ABO and Rh blood groups in volunteer non-remunerated blood donors of Rawalpindi/ Islamabad Methods: Record of blood donors from Jamila Sultana Thalassaemia Foundation was analyzed for ABO and Rh blood groups from Sept 2005 to Mar 2008. . Double/multiple entries were excluded. Results: Among voluntary blood donors 3519(79.5%) were males and 907(20.5%) were females. Blood group B+ve was the most frequent (31.2%). AB -ve was the least frequent (0.6%). Frequency of Blood groups A+ve, AB+ve, O+ve, A-ve, B-ve, and O - ve was 21.5%, 9.8%, 29.7%, 1.8%, 2.9%, and 2.5% respectively. The percentage of Rh+ and Rh- blood groups was 92.2% and 7.8% respectively. Conclusion: Blood group B+ was commonest and AB- was least frequent among donors. Rh+ blood group was 92.8%. There was no significant difference in males and female donors